Zdravstveni apsentizam i motivacija profesionalnih vatrogasaca - Bešter, Andrejka (Array, 2018)
Health absenteeism of employees impacts the performance of the organization. Therefore, what needs to be explored is motivation and other socially topical issues worth studying in relation to absenteeism. The research focused first on the relevant conceptual model that would show the relationship between health absenteeism and non-motivational factors for professional firefighters in Slovenia. The conceptual model was designed based on the review of domestic and foreign professional literature. The purpose was to determine if it is possible to have a beneficial effect on the rate of health absenteeism by using the appropriate or sufficient motivation. In the empirical part of the research we carried out a quantitative study on the relationship between health absenteeism and non-motivational factors. Questionnaires were distributed to 356 professional firefighters from 13 professional fire brigades in Slovenia. We found no relationships between job satisfaction or job performance and health absenteeism. Results gained from the research provide a theoretical and empirical contribution, and will be useful to theorists, researchers, and practitioners who study health absenteeism and motivation.